The Effect of Isomorphism Pressure and Accessibility of Financial Statements toward Stakeholder Trust with Financial Management Transparency as Mediation Variables (Study on Regional Government of the District/City in West Nusa Tenggara Province) (Global Journal of Management and Business Research, 2018)
This study aims to examine the effect of predicting the concept of isomorphism pressure and the accessibility of financial statements influencing stakeholder trust and examining the transparency prediction effects of financial management mediating isomorphism pressure and accessibility of financial statements on stakeholder trust This research was carried out on the Regional Government in Indonesia This type of explanatory research the sample is determined purposively Judgment sampling taken based on the criteria of financial management officials and internal supervision officials The hypothesis proposed in the study was four hypotheses based on institutional theory stewardship theory stakeholder theory signaling theory and analyzed using Partial Least Square 3 0 analysis tools
Keywords: isomorphism; accessibility; transparency; stakeholder